الإستجواب كوسيلة للرقابة السياسية في الدستور العراقي لعام 2005- دراسة تحليلية مقارنة - عمر, شورش حسن; سعيد, دانا عبدالكريم (Journal of Legal and Political Studies, 2013)
This research deals with the conditions of interrogation in the Iraqi Constitution of 2005 and the rules of procedure of the Iraqi Council of Representatives in 2007, in comparison with the position of the Egyptian legislature and Kuwaiti’s, as well as some other topics relating to interrogation, including mechanisms and discussion system of interrogation, indicating the situations that can provider of interrogation plea withdraw it, and those cases that lead to annulment of the plea. we found through research that the interrogation did not receive adequate attention by the Iraqi legislature, because its regulation was brief in the Constitution and the rules of procedure, which resulted in losing of some important issues, such as measures of notifying the government, including it in the Council's agenda and schedule a discussion, and the mechanism of the system is discussed in the Council, thus we have gave some observations and suggestions for addressing those gaps and deficiencies in the future.
Keywords: Iraqi Constitution of 2005; raqi Council of Representatives; Observation; interrogation